2018
DOI: 10.1002/jip.1504
|View full text |Cite
|
Sign up to set email alerts
|

Reducing tunnel vision with a pen‐and‐paper tool for the weighting of criminal evidence

Abstract: In order to prevent tunnel vision, and ultimately miscarriages of justice, police, prosecutors, and judges must remain open to alternative scenarios in which the suspect is in fact innocent. However, it is not evident from the literature that people are sufficiently aware of how alternative scenarios should be employed in the decision‐making process. In the present research, participants read a case vignette and formed an impression of the suspect's guilt. Some participants were made familiar with an alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 17 publications
0
18
1
Order By: Relevance
“…Participants were asked to rate police findings and to decide whether or not to convict the main suspect. Rassin (2018) found that the pen‐and‐paper tool counteracted an excessive focus on evidence confirming the main hypothesis in both lay people and criminal justice professionals. The pen‐and‐paper tool group also had a lower conviction rate than the alternative scenario group.…”
Section: Confirmation Biasmentioning
confidence: 74%
See 3 more Smart Citations
“…Participants were asked to rate police findings and to decide whether or not to convict the main suspect. Rassin (2018) found that the pen‐and‐paper tool counteracted an excessive focus on evidence confirming the main hypothesis in both lay people and criminal justice professionals. The pen‐and‐paper tool group also had a lower conviction rate than the alternative scenario group.…”
Section: Confirmation Biasmentioning
confidence: 74%
“…Ask & Granhag, 2005; Marksteiner, Ask, Reinhard, & Granhag, 2011; O'Brien, 2009). Rassin (2018) also found that participants showed tunnel vision in response to an incriminating case file. The findings of the current study are thus not in line with previous research, as the initial impression of guilt did not cause a preference for incriminating information.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, the motivation to be accurate in the guilty scenario increases, which also increases the likelihood of seeking information that confirms the presumption . Recent research has suggested that weighting criminal evidence using pencil and paper to make notes, whilst considering alternative scenarios, helps to reduce confirmation bias in criminal investigation contexts (see Rassin, 2018). Further examination of such a tool is warranted for the police-suspect interview and could be employed in the planning and preparation phases present in both the PEACE and the GIS framework.…”
Section: Future Directionsmentioning
confidence: 99%